All-ceramic prosthetic rehabilitation of a worn dentition: Use of a distal cantilever. Two-year follow-up - Usama N Chekhani; Aikaterini A Mikeli; Fabian K.P. Huettig (Wolters Kluwer Medknow Publications, 2013)
The rehabilitation of heavily abraded occlusion in patients with parafunctional habits is a restorative challenge to the dentist. Use of all-ceramic systems in such cases is widely considered, but uncertainty over their resistance hinders their broad use. The authors would like to illustrate a possible approach by mixing two all-ceramic systems based on zirconium dioxide and lithium disilicate. A 48-year-old female patient attended with reduced vertical dimension in a full dentition. She suffered from craniomandibular (CMD) pain and desired an esthetic rehabilitation. Prosthodontic treatment was started in a pain-free condition, after correction of the vertical dimension with an occlusal splint, over four months. Determination of the treatment was based on the clinical findings: IPS e.max® ZirCAD frameworks veneered with IPS e.max® Ceram were used for discolored retainers or subgingival finishing lines. All the rest received IPS e.max® Press crowns. A zirconia-based, single-tooth-retained distal cantilever reconstruction was used to replace a missing second molar. No technical or biological complication was observed 24 months after treatment. The patient was highly satisfied and pain-free.